SIW Circular Cavity Single Mode Filter With Triangle Probe - Siti Aminah Nordin; Mohd Khairul Mohd Salleh; Zuhani Ismail Khan; Norfishah Ab Wahab; Latifah Noh; Zakiah Mohd Yusoff (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
A novel substrate integrated waveguide (SIW) circular cavity using triangle probe are proposed in this paper. Prior to this research work, circular cavity resonator was used to achieve a miniaturization for the overall circuit size. The proposed filter provides single resonant mode, TE110. The resonant frequency of TE110 can be adjusted by varying the length and width of the SIW cavity. The proposed filter are designed to operate at frequency 3.75 GHz and implemented on Rogers 3210 substrate with thickness of 0.64 mm. The insertion loss in operating band is less than 0.6 dB and the return loss is better than 24 dB. Simulated result obtained using Ansoft HFSS software.